Entwicklung von Hilfsmitteln für die Planung und den Variantenvergleich von Beförderungssystemen in Gebäuden am Beispiel von Aufzügen - Drewer, Sebastian (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft / Hrsg.: Karlsruher Institut für Technologie, Lehrstuhl, 2016)
Sustainability represents a key factor in the construction and real estate sector by optimizing economical, ecological and social aspects of buildings. Transportation systems in buildings, as part of the technical building equipment, are not yet fully integrated into this concept. This work analyses the current approach of lift planning and design and develops supportive tools for neglected sections.